GABAergic modulation of serotonin release in the rat subfornical organ area. (6th September 2016) - Takahashi, Makoto; Nomura, Masahiko; Tanaka, Junichi
Highlights: Perfusion with the GABAA antagonist through a microdialysis probe enhances 5-HT in the SFO. Higher perfusion with the GABAA or GABAB agonist reduces the 5-HT levels. The GABAA agonist attenuates the hypovolemia-increase in the 5-HT. Muscimol, but not baclofen, affects in the 5-HT-mediated body fluid balance in the SFO. Abstract: The present study was carried out to examine whether γ–aminobutyric acid (GABA) receptor mechanisms are involved in the release of serotonin (5-hydroxytryptamine, 5-HT) in the subfornical organ (SFO) using intracerebral microdialysis techniques. Perfusion with the GABA receptor antagonists as well as agonists was performed in the region of the SFO through a microdialysis probe and extracellular concentrations of 5-HT and its metabolite 5-hydroxyindoleacetic acid (5-HIAA) were measured in freely moving rats. Perfusion with the GABAA receptor antagonist bicuculline (10 and 50 μM), but not the GABAB receptor antagonist phaclofen (10 and 50 μM), increased dialysate 5-HT and 5-HIAA concentrations in the SFO area, suggesting that the GABAergic system may tonically inhibit the 5-HT release in the SFO area through GABAA receptors. Higher perfusion with the GABAA receptor agonist muscimol (50 μM) or the GABAB receptor agonist baclofen (250 μM) decreased extracellular levels of 5-HT and 5-HIAA in the SFO area. Nonhypotensive hypovolemia induced by subcutaneous injection of polyethylene glycol (PEG, 30%, 5 ml) significantly enhanced the 5-HT and 5-HIAA concentrations in the SFO area. The enhanced 5-HT and 5-HIAA levels elicited the PEG treatment were reduced by perfusion with muscimol (10 μM), but not by baclofen (50 μM). These results show the involvement of both GABAA and GABAB receptors in the modulation of the 5-HT release in the SFO area, and imply that the GABAA receptor mechanism may be importance for the serotonergic regulatory system of body fluid balance.